2013
DOI: 10.1371/journal.pone.0076346
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1 Downregulates COX-2 Expression Leading to Decrease of PGE2 Production in Human Lung Cancer A549 Cells, Which Is Involved in Fibrotic Response to TGF-β1

Abstract: Transforming growth factor-ß1 (TGF-β1) is a multifunctional cytokine that is involved in various pathophysiological processes, including cancer progression and fibrotic disorders. Here, we show that treatment with TGF-β1 (5 ng/mL) induced downregulation of cyclooxygenase-2 (COX-2), leading to reduced synthesis of prostaglandin E2 (PGE2), in human lung cancer A549 cells. Treatment of cells with specific inhibitors of COX-2 or PGE2 receptor resulted in growth inhibition, indicating that the COX-2/PGE2 pathway co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 52 publications
1
41
0
Order By: Relevance
“…Many critical steps in intracellular TGF-β signaling are mediated by Smad proteins. However, Smad-independent signaling transduction pathways are also involved in the biological activities of TGF-β [13,14]. As the Smad pathway principally regulates gene expression, it was originally thought that nonSmad effectors mediate the rapid or direct effects of TGF-β on tumor invasiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Many critical steps in intracellular TGF-β signaling are mediated by Smad proteins. However, Smad-independent signaling transduction pathways are also involved in the biological activities of TGF-β [13,14]. As the Smad pathway principally regulates gene expression, it was originally thought that nonSmad effectors mediate the rapid or direct effects of TGF-β on tumor invasiveness.…”
Section: Introductionmentioning
confidence: 99%
“…8). TGF-␤ has previously been characterized to have dual effects on COX-2 (24,36,45,51,56). A study in human nonsmall cell lung cancer A549 cells showed that TGF-␤ was able to downregulate COX-2 (56).…”
Section: Discussionmentioning
confidence: 99%
“…VEGF increases the secretion of various proteases and matrix degradation enzymes in tumors, further contributing to tumor invasion and metastasis [36]. TGF-β1 is a multifunctional cytokine that regulates various physiological processes such as cell growth, differentiation, immune suppression, extracellular matrix deposition, and tumorigenesis [37][38][39]. Several studies demonstrated that TGF-β1 promotes tumor metastasis, angiogenesis, and escape from immune surveillance and is secreted in several cancers such as breast and lung cancers [38,[40][41][42].…”
Section: Discussionmentioning
confidence: 99%